Communication and media theories - Campos, Patrick ;Solis, Randy Jay ;Pangilinan, Choy (Diliman Quezon City, Philippines : The University of the Philippines Press, 2014)
The Media and Communication Textbook Series is jointly published by the Office of Research and publication of the University of the Philippines College of Mass communication and the University of the Philippines Press.
Part 1. Overall Introduction -- Part 2. Introduction to positivist theory -- Part 3. Toward a critical view of Media -- Part 4. Media Studies in the context of Philippine studies -- Part 5. Integration/Synthesis.
Includes bibliographical references.
Keywords: MASS MEDIA -- PHILIPPINES -- SOCIAL ASPECTS